Fundamentals of mental health nursing - Neeb, Kathy, 1952- (Philadelphia : F.A. Davis Co., 2008)
"Kathy Neeb continues to address mental health within the scope of practical/vocational nursing in this updated edition, emphasizing that, as an LPN/LVN, you will most commonly care for patients with psychiatric problems in general patient care settings rather than in specialized psychiatric facilities. This targeted approach, along with her conversational writing style, clearly addresses the most pertinent topics in the care settings in which most LPNs work. Also included in this updated edition: completely revised and updated coverage of psychopharmaceuticals; integration of DSM-IV-TR into all discussions; enhanced coverage of palliative and restorative care; new coverage on facing the reality of terrorism integrated throughout relevant chapters; and more detailed exploration of religious and cultural beliefs and their impact on mental health and treatment."--BOOK JACKET.
nrs
Keywords: Psychiatric nursing; Practical nursing; Mental Disorders -- nursing; Nursing, Practical; Psychiatric Nursing -- methods